COVID-19 in the Perioperative Period of Cardiovascular Surgery: the Brazilian Experience - Gomes,Walter J. (2021)
Abstract Introduction: We investigated the clinical course and outcomes of patients submitted to cardiovascular surgery in Brazil and who had developed symptoms/signs of coronavirus disease 2019 (COVID-19) in the perioperative period. Methods: A retrospective multicenter study including 104 patients who were allocated in three groups according to time of positive real time reverse transcriptase-polymerase chain reaction (RT-PCR) for the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2): group 1, patients who underwent cardiac surgery > 10 days after positive RT-PCR; group 2, patients with a positive RT-PCR within 10 days before or after surgery; group 3, patients who presented positive RT-PCR > 10 days after surgery. The primary outcome was mortality and secondary outcomes were postoperative complications, intensive care unit (ICU) length of stay, and postoperative days of hospitalization. Results: The three groups were similar with respect to age, the European System of Cardiac Operative Risk Evaluation score, and comorbidities, except hypertension. Postoperative complications and death were significantly higher in groups 2 and 3 than in group 1, and no significant difference between groups 2 and 3 was seen. Group 2 showed a high prevalence of surgery performed as an urgent procedure. Although no significant differences were observed in ICU length of stay, total postoperative hospitalization time was significantly higher in group 3 than in groups 1 and 2. Conclusion: COVID-19 affecting the postoperative period of patients who underwent cardiovascular surgery is associated with a higher rate of morbidity and mortality. Delaying procedures in RT-PCR-positive patients may help reduce risks of perioperative complications and death.